Evaluating the impact of object-oriented design on software quality - Brito e Abreu, F.; Walcelio Melo (Proceedings of the 3rd International Software Metrics Symposium (METRICS'96), 1996)
This paper describes the results of a study where the impact of object-oriented (OO) design on software quality characteristics is experimentally evaluated. A suite of Metrics for OO Design (MOOD) was adopted to measure the use of OO design mechanisms. Data collected on the development of eight small-sized information management systems based on identical requirements were used to assess the referred impact. Data obtained in this experiment show how OO design mechanisms such as inheritance, polymorphism, information hiding and coupling, can influence quality characteristics like reliability or maintainability. Some predictive models based on OO design metrics are also presented.